Hybrid Financial Innovation: A Sustainable Economic Recovery Model for OIC Nations - Md Sajidur Rahman; Tarekol Islam Maruf; Noor Adila Binti Abd. Raub; Maniyarasi Gowindasamy (Muslim Business and Economics Review, 2025)
Global financial shocks, such as COVID-19, and systemic vulnerabilities dramatically threaten the world's economic resilience. These significant events have revealed economic weakness, especially in Organisation of Islamic Cooperation (OIC) member states and other developing nations, resulting in significant job losses, manufacturing disturbances, fiscal imbalances, recessions, and deflationary issues. There is a growing concern that existing economic recovery frameworks lack the capacity to support long-term financial resilience and equitable growth. This study examines a comprehensive framework to disclose a resilient economic recovery model that mitigates shocks and leads to sustainability in developing and OIC countries. This study also proposes a hybrid financial innovation model that ascertains government-backed crisis funds with Islamic financing mechanisms. This model can ensure sustainable agricultural funding and promote long-term economic resilience, and has the potential to save a shocked economy from recessions. This study adopts a qualitative case study research approach and combines sustainable economic modeling and a consistent funding framework that is adaptable to OIC nations such as Pakistan, Indonesia, Saudi Arabia, Turkey, Bangladesh, Egypt, Iran, and Malaysia. The study’s findings provide a practical roadmap for policymakers, ensuring that agricultural financing remains stable during economic shocks and recessional periods through the support of universal financial strategies. Additionally, this study contributes to policy innovation by offering a sustainable, debt-free funding roadmap that can be adapted for crises as well as post-crisis recovery in both developing and Islamic economies to guarantee fiscal sustainability and enable the conversion of economic weaknesses into strategic advantages.